18TH CENTURY BOOKS ON POETICS IN GERMAN AVAILABLE FOR DONELAITIS DURING HIS STUDY TIME - MICHELINI, GUIDO (Knygotyra, 2015)
The paper is based on the hypothesis that the most important sources of Kristijonas Donelaitis’ poetic theory might have been some books in German about poetics, which were popular in Prussia in the first half of the 18th century. In all probability, the poet read these books between 1736 and 1740, during his study time at the University of Konigsberg, rather than later, when he was interested in other subjects (such as music and theology), and moreover living in small provincial centres without access to any specialized libraries. Since it is assumed that the most influential of these publications was the treatise Versuch einer Anleitung Zur Deutschen Poesie, published in 1732 in Konigsberg and written by Donelaitis’ teacher Heinrich Arnoldt, professor of theology at Konigsberg’s University, the paper pays great attention to this work by proposing a detailed analysis of it. It is also pointed out how Arnoldt’s book, together with Morlin’s treatise Principium primarium in lingva Lithvanica, influenced Donelaitis’ choice to write his poem in a popular style; in addition, the book could have influenced Donelaitis’ pietistic ideology. The paper ends with a shorter analysis of other two books, cited by Arnoldt, with which Donelaitis could have been likewise acquainted during his study time at the university: Gottsched’s Versuch einer Critischen Dichtkunst vor die Deutschen (1730) and the anonymous treatise Anleitung zur Poesie, Darinnen ihr Ursprung, Wachsthum, Beschaffenheit und rechter Gebrauch untersuchet und gezeiget wird (1725).